21st Century Pre-School Bilingual Education 2020
DOI: 10.4324/9781351189279-2
|View full text |Cite
|
Sign up to set email alerts
|

Two languages in the air: a cross-cultural comparison of preschool teachers’ reflections on their flexible bilingual practices

Abstract: M. (2018). Two languages in the air : a cross-cultural comparison of preschool teachers' reflections on their flexible bilingual practices. In M. Schwartz, & Å. Palviainen (Eds.), 21st Century Pre-school Bilingual Education. Routledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…In particular, the project investigated bilingual practices of Swedish-Finnish bilingual children in Swedish-medium preschools through interviews with 18 parents, 10 preschool staff, and 9 children, observations in the family settings and preschools for 6 months, and a document analysis of mass media and policy documents and curricula. The project revealed important findings including a shift to flexible bilingual practices in the classroom by taking each child's needs and interests into account (Palviainen et al 2016), the importance of establishing partnerships beginning from the early childhood years to promote bilingualism at home and in the society (Bergroth and Palviainen 2016), and the active agency of preschoolers in constructing the language policies at home and at school (Bergroth and Palviainen 2017). Overall, the findings expanded our understanding of FLP, and the partnership between families and educators.…”
Section: Flp and Mainstream Early Childhood Institutionsmentioning
confidence: 86%
“…In particular, the project investigated bilingual practices of Swedish-Finnish bilingual children in Swedish-medium preschools through interviews with 18 parents, 10 preschool staff, and 9 children, observations in the family settings and preschools for 6 months, and a document analysis of mass media and policy documents and curricula. The project revealed important findings including a shift to flexible bilingual practices in the classroom by taking each child's needs and interests into account (Palviainen et al 2016), the importance of establishing partnerships beginning from the early childhood years to promote bilingualism at home and in the society (Bergroth and Palviainen 2016), and the active agency of preschoolers in constructing the language policies at home and at school (Bergroth and Palviainen 2017). Overall, the findings expanded our understanding of FLP, and the partnership between families and educators.…”
Section: Flp and Mainstream Early Childhood Institutionsmentioning
confidence: 86%
“…From February 2017, thus, 9 months into the PD, the three practitioners begun to use translanguaging more strategically. They spoke some French, Spanish, and Portuguese to French-speaking, Spanish-speaking, and Portuguese-speaking children when they judged that this switch promoted learning (Mård-Miettinen et al 2018;Mifsud and Vella 2018;Palviainen et al 2016). Translanguaging enabled the teachers to increase the quantity of input and improve the quality of the adult-child interactions.…”
Section: Professional Learning Outcomesmentioning
confidence: 99%
“…In all settings, the teachers and caregivers translanguaged and translated to gain and sustain attention, facilitate communication, ensure comprehension, or make children feel secure (Mård-Miettinen et al 2018;Mifsud and Vella 2018). Yet, the practitioners in the formal settings monitored their language use more carefully than those in the non-formal sector, and their translanguaging resembled the "responsible code-switching" described by García (2009) and Palviainen et al (2016). By contrast, the practitioners in the non-formal educational institutions in Luxembourg switched to the child's home languages without always considering the need for such a switch.…”
Section: Critical Issues and Topics Reflexivitymentioning
confidence: 99%
“…The data included three 60-minute interviews with her as well as two half-day video-recorded observations of her interaction with the children. The interviews, which have been reported in more detail in Palviainen and Mård-Miettinen (2015) and Palviainen et al (2016), were of a stimulated recall type: the bilingual teacher watched the video-recordings of her interaction with the children in small group activities that she had led and commented on and explained her own bilingual language practices. The principles she described herself as following and the practices she applied are explained further in the following section (4.2).…”
Section: Research Design and Data Collectionmentioning
confidence: 99%
“…Previous analyses of her bilingual practices when leading small group activities have shown that she followed certain principles in her use of the two languages: a) she flexibly and continuously alternated between the two languages, b) she used the two languages to equal amounts across activities, c) she adhered to responsible codeswitching, avoiding direct translation between the two languages and using the two languages for different purposes, d) she used rich scaffolding structures (body language, contextualisation, verbalisation of actions, repetition of words and routines, etc. ), and e) she adjusted her bilingual speech to the needs of individual children (for more details see Palviainen et al 2016). She also emphasised the importance of acting as a role model of a bilingual speaker.…”
Section: Participantsmentioning
confidence: 99%